Single-event-effects on a flash FPGA for satellites - Fang, Ao (Nanyang Technological University, 2024)
The space industry has now evolved from “Traditional Space” to “New Space”. Traditional Space involves large geostationary satellites embodying mostly space grade electronics while New Space involves small Low-Earth-Orbit satellites embodying mostly Commercially-Off-The-Shelf (COTS) electronics. However, most COTS electronics, such as the COTS Field Programmable Gate Array (FPGA), typically suffer from radiation effects in space, specifically Single-Event Effects (SEEs) which may render mission failure. The specific SEEs include Single-Event-Latchups (SELs) and Single-Event-Upsets (SEUs).